Pasture and subsequent feedlot performance by beef cattle grazing acremonium coenophialuminfectedtall fescue and offered different levels of ground grain sorghum - Freeman, A.S.; Coffey, K.P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty-six crossbred steers and sixty-three crossbred heifers (704 lb BW) were used to evaluate the effects of energy supplementation on animal performance during grazing of endophyte-infected tall fescue and on subsequent feedlot performance. Grazing ADG increased linearly (P<.05) from .70 lb/d for control (no supplementation) to .93 and 1.12 lb/d for cattle receiving .25% and .5% of BW as ground sorghum grain (SG), respectively. Initial feedlot weight was increased linearly (P<.02) by pasture SG levels. Feedlot daily gain, dry matter intake, and feed conversion; carcass characteristics; and liver abscess scores were not affected (P>.10) by SG that had been fed on pasture.
Keywords: Beef; Sorghum grain; Steers; Heifers; Grazing performance; Feedlot performance; Carcass merit; Fescue; Endophyte